Case Sudy: Construction Of Soil Stabilization On Hauling Roads At A Nickel Mining Site In Souteast Sulawesi, Indonesia - Tilaka Wasanta; Elshaan Helmmie; Edwin Laurencis (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Haul roads play an important role in supporting nickel mining operations, as their condition directly affects transportation efficiency and production performance. Inadequate road conditions can lead to reduced operational effectiveness. Thus, improving subgrade strength is necessary to ensure adequate pavement performance. This study investigated the use of cement as a soil stabilizing agent to enhance the engineering properties of haul road materials. The laboratory test results showed that the addition of 3.00% cement increased the California Bearing Ratio (CBR) from 55.87% to 168.80% after 3 days of curing. The stabilized material also achieved an Unconfined Compressive Strength (UCS) of 4.086 MPa after 28 days of curing. Pavement structural design subsequently evaluated using the Austroads (2017) method based on both laboratory test results and actual field conditions. The analysis indicated that the pavement structure could support traffic loading of up to 79.78 × 10? Equivalent Standard Axles (ESA) under laboratory conditions and 44.40 × 10? ESA under field conditions. The results demonstrate that cement stabilization can substantially improve subgrade strength and increase the structural capacity of haul road pavements, making it a viable alternative for supporting heavy mining traffic.